2017
DOI: 10.5808/gi.2017.15.3.82
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Microarray Testing in 42 Korean Patients with Unexplained Developmental Delay, Intellectual Disability, Autism Spectrum Disorders, and Multiple Congenital Anomalies

Abstract: Chromosomal microarray (CMA) is a high-resolution, high-throughput method of identifying submicroscopic genomic copy number variations (CNVs). CMA has been established as the first-line diagnostic test for individuals with developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), and multiple congenital anomalies (MCAs). CMA analysis was performed in 42 Korean patients who had been diagnosed with unexplained DD, ID, ASDs, and MCAs. Clinically relevant CNVs were discovered in 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…MCAs are defined as multiple major structural malformations that cannot be explained by an underlying syndrome or sequence. These disorders might have a genetic etiology involving the gains and losses of CNVs and loss of heterozygosity (LOH), and the clinical consequences of these rearrangements are commonly associated with location, size, and the gene content (Figures 2 and 3) [32][33][34].…”
Section: Application In the Diagnosis Of Human Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…MCAs are defined as multiple major structural malformations that cannot be explained by an underlying syndrome or sequence. These disorders might have a genetic etiology involving the gains and losses of CNVs and loss of heterozygosity (LOH), and the clinical consequences of these rearrangements are commonly associated with location, size, and the gene content (Figures 2 and 3) [32][33][34].…”
Section: Application In the Diagnosis Of Human Diseasesmentioning
confidence: 99%
“…Using the combining SNPs with customized exon-targeted oligonucleotide array in a cohort of 3240 patients, Wiszniewska et al [24] provided a comprehensive approach for the identification of clinically relevant copy number neutral changes in addition to CNVs in a single assay. A study using CMA for 42 Korean patients with unexplained DD, ID, ASD, and MCA identified clinically relevant CNVs in 66.6% of patients [33]. Therefore, microarray-based technologies have become a powerful tool for the identification of genomic rearrangements smaller than 5 Mb that are associated with neurodevelopmental disorders.…”
Section: Application In the Diagnosis Of Human Diseasesmentioning
confidence: 99%
“…The use of NGS for diagnosing DMD also had recently been in the spotlight [ 9 ]. Chromosomal microarray analysis (CMA) can also be used to identify the underlying congenital causes of unexplained developmental delay [ 10 ]. To the authors’ knowledge, the diagnostic application of NGS and CMA for infantile presymptomatic DMD has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%